D2-40 AS A POTENTIAL MARKER THAT DIFFERENTIATE VERRUCOUS CARCINOMA FROM SQUAMOUS CELL PAPILLOMA (Iraqi Journal of Medical Sciences, 2016)
Background: Verrucous carcinoma is a distinct variant of oral squamous cell carcinoma characterized by slow growth and rare metastases. It may present diagnostic difficulties as it may be inaccurately diagnosed as squamous cell papilloma.Objective:The study performed a comparative immunohistochemical staining for both entities to obtain a possible method of differentiation.Methods:The study involved 13 samples of oral verrucous carcinomas and 10 samples of oral squamous cell papillomas which were stained immunohistochemically with antibodies to the lymphatic endothelial marker D240.Results:In all samples, the entire epithelium of verrucous carcinomas was positively stained with D240 whereas only the basal cell layer of squamous cell papillomas was positive.Conclusion: D240 could be used as a differentiating marker between oral verrucous carcinomas and squamous cell papillomas.Keywords: Verrucous carcinoma, Squamous cell papillomas, D240.
Keywords: Verrucous carcinoma; Squamous cell papillomas; D240